Análisis De La Satisfacción Del Profesorado De La Escuela Rural En La Provincia De Granada (España) RespectoASu Relación PersonalYProfesional Con La Comunidad Educativa - Sánchez, Francisco Raso; Marín, José Antonio Marín; García, Antonio Manuel Rodríguez (European Scientific Journal, ESJ, 2017)
The importance recently acquired by satisfaction studies in educational institutions has caused scientific interest in the welfare of members of the educational community to increase significantly, given the relationship of this variable, not only to labor productivity, but to the quality of interpersonal relationships within our schools, which is especially necessary in those of rural type. In this regard, we present the following study, funded by the Ministry of Education, Culture and Sports of Spain with the reference AP2007 – 00294, and whose interest focused on knowing those aspects of social interactions with the rest of the members of the educational community of rural schools in the province of Granada more pleasing and displeasing to their teachers respectively. For this purpose, a descriptive and non-experimental research, focused on the implementation of the survey technique on a sample of 221 teachers in Grenadian rural public schools was designed. Thanks to this methodology, it has been found that rural teachers in Granada value far more the daily support and the friendship of the rest of their coworkers than the involvement of the families in the education of their children or the cooperation of the public administration with the problems of rural educational centers, a result already supported by other scientific research carried out on the subject in the same context.